A method for preparing basalt fiber composite photovoltaic bracket material

By combining basalt fibers with epoxy vinyl resin and adding specific additives and process steps, the problem of insufficient mechanical properties and durability of existing photovoltaic scaffold materials is solved, and higher longitudinal tensile strength, full-section compression performance and ultraviolet resistance are achieved.

CN118852851BActive Publication Date: 2025-03-25SICHUAN ZHONGHUI CHUANGDA NEW MATERIAL TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411096254.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-03-25
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

The existing photovoltaic bracket materials have a large specific gravity, low longitudinal tensile strength, poor full-section compression performance, and poor stability and durability.

Method used

Basalt fibers are combined with bisphenol A-type epoxy vinyl resin, and coupling agents, film forming agents, lubricants and UV-proof synergists are added to prepare photovoltaic scaffold materials with improved mechanical properties and durability through specific process steps and curing conditions.

Benefits of technology

The longitudinal tensile strength, full-section compression performance and durability of photovoltaic bracket materials have been significantly improved, especially in terms of ultraviolet resistance, and the service life has also been extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a preparation method of a basalt fiber composite photovoltaic bracket material, and relates to the technical field of photovoltaic bracket materials. The present invention soaks basalt fiber in bisphenol A type epoxy vinyl ester resin, adds coupling agent, film-forming agent, lubricant, and UV protection agent, stirs and mixes evenly, pours into a mold, heats and solidifies to form, and extrudes the mold to obtain a basalt fiber composite photovoltaic bracket material; the benzimidazolone and carborane structures introduced in the present invention enhance the chemical stability of the material, especially the absorption and shielding ability of ultraviolet rays, thereby effectively extending the service life of outdoor products such as photovoltaic brackets; the introduction of yttrium complexes may increase the cross-linking density of the material, thereby improving the mechanical properties of the cured material; the photovoltaic bracket of the present invention includes: columns, main beams, purlins, and struts; the main beam is supported by columns below; the purlins are fixed on the main beams; one end of the struts is fixed on the main beams, and the other end is fixed on the columns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic support materials, and in particular to a method for preparing a basalt fiber composite photovoltaic support material. Background Art

[0002] With the development of the photovoltaic industry, lightweight photovoltaic bracket structures and extreme application environments have become a development trend. High-performance fiber-reinforced composite materials among composite materials are the preferred materials for lightweight photovoltaic bracket structures and are also indispensable materials for use in extreme environments.

[0003] Chinese patent CN106589592A: A non-metallic solar photovoltaic bracket material, prepared from the following substances and their mass contents: 80 parts of polypropylene, 0-20 parts of inorganic filler, 0-1 part of carbon black, 0.1-5 parts of nanomaterials, 0.1-0.5 parts of composite antioxidants, and 0.1-0.5 parts of composite anti-ultraviolet agents.

[0004] Chinese patent CN110527239A: relates to the field of photovoltaic technology, especially a non-metallic solar photovoltaic bracket material and its preparation method; its mass composition is as follows: 10-20 parts of a polymer of acrylonitrile, butadiene and styrene, 1-3 parts of graphene, 0.2-4.8 parts of nanomaterials, 1.2-3.6 parts of composite flame retardants, and 0.2-0.48 parts of composite anti-aging agents.

[0005] Chinese patent CN111303587A: discloses a multi-fiber composite resin-based photovoltaic bracket material, which is composed of the following raw materials in parts by weight: 5-7 parts of isopropyl alcohol, 3-4 parts of 2,2-dihydroxymethylpropionic acid, 100-130 parts of epoxy resin, 1-2 parts of tristearate, 10-15 parts of epoxy modified fiber, 3-5 parts of dodecyl primary amine, and 0.8-1 parts of stannous sulfide.

[0006] However, the photovoltaic brackets prepared by the current public technology have disadvantages such as large specific gravity, low longitudinal tensile strength, poor full-section compression performance, poor stability, and poor durability.

[0007] In view of the above reasons, the present invention provides a method for preparing a basalt fiber composite photovoltaic support material. Summary of the invention

[0008] In a first aspect, the present invention provides a method for preparing a basalt fiber composite photovoltaic bracket material, the operating steps of which are:

[0009] S1: Place 10-20 parts of basalt fiber into 60-80 parts of bisphenol A epoxy vinyl ester resin and soak for 10-20 minutes;

[0010] S2: Continue to add 0.1-0.3 parts of coupling agent, 0.5-1 parts of film-forming agent, 0.3-0.7 parts of lubricant, and 0.5-1 parts of UV protection synergist, and stir and mix evenly to obtain a mixture;

[0011] S3: pouring the mixture into a mold, heating and curing it into shape, and then cooling it to room temperature;

[0012] S4: The formed product is pulled out of the mold to obtain a basalt fiber composite photovoltaic bracket material.

[0013] Furthermore, the coupling agent is one of KH550, KH560, KH570, and KH792.

[0014] Furthermore, the film-forming agent is one of an acrylic resin film-forming agent, a butadiene resin film-forming agent, an epoxy polyurethane film-forming agent, and a polyester polyurethane film-forming agent.

[0015] Furthermore, the lubricant is hexadecyltrimethylammonium bromide or polyacrylamide.

[0016] Furthermore, the curing temperature is 150-180° C. and the curing time is 4-7 hours.

[0017] Furthermore, the pultrusion speed is 200-300 mm / min.

[0018] In a second aspect, the present invention provides a method for preparing the above-mentioned UV protection synergist:

[0019] A1: By weight, 0.2-3.5 parts of 10,13-epoxy-10,12-octadecadienoic acid, 1-4 parts of yttrium nitrate, and 100-200 parts of tetrahydrofuran are stirred and mixed, and reacted at 40-50° C. for 30-100 minutes;

[0020] A2: Add 12-15 parts of 1,2-dimercapto-o-carborane, 0.2-2 parts of 1-(2-propenyl)-2-benzimidazolone, and 2-4 parts of triethylamine, raise the temperature to 50-63°C and stir for 100-120 minutes, and distill off tetrahydrofuran to obtain an anti-ultraviolet synergist.

[0021] In a third aspect, the photovoltaic support described in the present method includes: columns, main beams, purlins, and struts; the main beams are supported from below by columns; the purlins are fixed to the main beams; one end of the struts is fixed to the main beams, and the other end is fixed to the columns.

[0022] Reaction mechanism

[0023] 1. Mercapto-epoxy ring-opening reaction

[0024] Reaction start: First, the epoxy group in yttrium 10,13-epoxy-10,12-octadecadienoate is easily attacked by nucleophiles due to its large ring tension; 1,2-dithiol-o-carborane is a nucleophile, and its thiol group carries a lone pair of electrons, which can attack the carbon atom of the epoxy group;

[0025] Ring-opening mechanism: After the epoxy group is attacked, a ring-opening reaction occurs to form a hydroxyl group and open the carbon-oxygen bond; during this process, the thiol group of the carborane forms a covalent bond with the carbon atom of the epoxy group, while the oxygen on the epoxy group forms a hydrogen bond with another thiol hydrogen on the carborane, thereby stabilizing the ring-opening product.

[0026] 2. Mercapto-propylene addition reaction

[0027] Michael addition: The propenyl group in 1-(2-propenyl)-2-benzimidazolone acts as an acceptor and undergoes a Michael addition reaction with the thiol group in 1,2-dithiol-o-carborane; the lone pair of electrons of the thiol group attacks the β-carbon (i.e., the terminal carbon) of the propenyl group, resulting in the cleavage of the double bond;

[0028] Product formation: This reaction ultimately forms a new sigma bond between the β-carbon of the propenyl group and the thiol group; as a result, the benzimidazolone and the carborane are linked via a thioether link to form a stable addition product.

[0029] Technical Effects

[0030] 1. Improve weather resistance and UV resistance

[0031] Chemical stability: The introduced benzimidazolone and carborane structures enhance the chemical stability of the material, especially its ability to absorb and shield ultraviolet rays, thus effectively extending the service life of outdoor products such as photovoltaic brackets;

[0032] UV protection mechanism: The carborane structure has a unique three-dimensional framework that can effectively scatter and absorb ultraviolet rays, reduce photooxidation, and protect the material from aging;

[0033] 2. Promote the improvement of comprehensive performance of materials

[0034] Improved mechanical properties: The introduction of yttrium complexes may increase the cross-linking density of the material, thereby enhancing the mechanical strength and thermal stability after curing;

[0035] Improved temperature resistance: The newly formed chemical structure is stable, which helps to improve the operational stability and service life of the material in high temperature environments, which is especially important for outdoor applications such as photovoltaic brackets. DETAILED DESCRIPTION

[0036] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] Longitudinal tensile strength, full-section compression performance, and durability performance (longitudinal tensile strength retention rate of UV resistance for 1000h) tests: refer to GB / T31539-2015 "Fiber-reinforced composite pultruded profiles for structures" for testing.

[0038] Example 1

[0039] A method for preparing a basalt fiber composite photovoltaic bracket material, the operating steps of which are:

[0040] S1: 10g of basalt fiber was placed in 60g of bisphenol A epoxy vinyl ester resin and soaked for 10min;

[0041] S2: Continue to add 0.1 g of coupling agent, 0.5 g of film-forming agent, 0.3 g of lubricant, and 0.5 g of UV protection enhancer, and stir and mix well to obtain a mixture;

[0042] S3: pouring the mixture into a mold, heating and curing it into shape, and then cooling it to room temperature;

[0043] S4: The formed product is pulled out of the mold to obtain a basalt fiber composite photovoltaic bracket material.

[0044] The coupling agent is KH550.

[0045] The film-forming agent is an acrylic resin film-forming agent.

[0046] The lubricant is hexadecyltrimethyl quaternary ammonium bromide.

[0047] The curing temperature is 150° C. and the curing time is 4 hours.

[0048] The pultrusion speed is 200 mm / min.

[0049] The preparation method of the anti-ultraviolet synergist is:

[0050] A1: 0.2 g of 10,13-epoxy-10,12-octadecadienoic acid, 1 g of yttrium nitrate and 100 g of tetrahydrofuran were stirred and mixed, and reacted at 40° C. for 30 min;

[0051] A2: Add 12g 1,2-dimercapto-o-carborane, 0.2g 1-(2-propenyl)-2-benzimidazolone and 2g triethylamine, raise the temperature to 50°C and stir for 100min, distill off tetrahydrofuran to obtain an anti-ultraviolet synergist.

[0052] The photovoltaic support comprises: columns, main beams, purlins, and struts; the main beams are supported by columns below; the purlins are fixed on the main beams; one end of the struts is fixed on the main beams, and the other end is fixed on the columns.

[0053] Example 2

[0054] A method for preparing a basalt fiber composite photovoltaic bracket material, the operating steps of which are:

[0055] S1: 13g of basalt fiber was placed in 65g of bisphenol A epoxy vinyl ester resin and soaked for 15min;

[0056] S2: Continue to add 0.2 g of coupling agent, 0.6 g of film-forming agent, 0.4 g of lubricant, and 0.6 g of UV protection synergist, and stir to mix evenly to obtain a mixture;

[0057] S3: pouring the mixture into a mold, heating and curing it into shape, and then cooling it to room temperature;

[0058] S4: The formed product is pulled out of the mold to obtain a basalt fiber composite photovoltaic bracket material.

[0059] The coupling agent is KH560.

[0060] The film-forming agent is a butadiene resin film-forming agent.

[0061] The lubricant is hexadecyltrimethyl quaternary ammonium bromide.

[0062] The curing temperature is 160° C. and the curing time is 5 hours.

[0063] The pultrusion speed is 240 mm / min.

[0064] The preparation method of the anti-ultraviolet synergist is:

[0065] A1: 1 g of 10,13-epoxy-10,12-octadecadienoic acid, 2 g of yttrium nitrate and 140 g of tetrahydrofuran were stirred and mixed, and reacted at 45°C for 50 min;

[0066] A2: Add 13 g of 1,2-dimercapto-o-carborane, 1 g of 1-(2-propenyl)-2-benzimidazolone, and 3 g of triethylamine, raise the temperature to 55°C and stir for 105 min, and distill off tetrahydrofuran to obtain an anti-ultraviolet synergist.

[0067] The photovoltaic support comprises: columns, main beams, purlins, and struts; the main beams are supported by columns below; the purlins are fixed on the main beams; one end of the struts is fixed on the main beams, and the other end is fixed on the columns.

[0068] Example 3

[0069] A method for preparing a basalt fiber composite photovoltaic bracket material, the operating steps of which are:

[0070] S1: 18g of basalt fiber was placed in 75g of bisphenol A epoxy vinyl ester resin and soaked for 15min;

[0071] S2: Continue to add 0.2 g of coupling agent, 0.8 g of film-forming agent, 0.6 g of lubricant, and 0.8 g of UV protection synergist, and stir to mix evenly to obtain a mixture;

[0072] S3: pouring the mixture into a mold, heating and curing it into shape, and then cooling it to room temperature;

[0073] S4: The formed product is pulled out of the mold to obtain a basalt fiber composite photovoltaic bracket material.

[0074] The coupling agent is KH570.

[0075] The film-forming agent is an epoxy polyurethane film-forming agent.

[0076] The lubricant is polyacrylamide.

[0077] The curing temperature is 170° C. and the curing time is 6 hours.

[0078] The pultrusion speed is 280 mm / min.

[0079] The preparation method of the anti-ultraviolet synergist is:

[0080] A1: 3 g of 10,13-epoxy-10,12-octadecadienoic acid, 3 g of yttrium nitrate and 180 g of tetrahydrofuran were stirred and mixed, and reacted at 45°C for 80 min;

[0081] A2: Add 14 g 1,2-dimercapto-o-carborane, 1.5 g 1-(2-propenyl)-2-benzimidazolone and 3 g triethylamine, raise the temperature to 60°C and stir for 115 min, distill off tetrahydrofuran to obtain an anti-ultraviolet synergist.

[0082] The photovoltaic support comprises: columns, main beams, purlins, and struts; the main beams are supported by columns below; the purlins are fixed on the main beams; one end of the struts is fixed on the main beams, and the other end is fixed on the columns.

[0083] Example 4

[0084] A method for preparing a basalt fiber composite photovoltaic bracket material, the operating steps of which are:

[0085] S1: 20g of basalt fiber was placed in 80g of bisphenol A epoxy vinyl ester resin and soaked for 20min;

[0086] S2: Continue to add 0.3 g of coupling agent, 1 g of film-forming agent, 0.7 g of lubricant, and 1 g of UV protection enhancer, stir and mix evenly to obtain a mixture;

[0087] S3: pouring the mixture into a mold, heating and curing it into shape, and then cooling it to room temperature;

[0088] S4: The formed product is pulled out of the mold to obtain a basalt fiber composite photovoltaic bracket material.

[0089] The coupling agent is KH792.

[0090] The film-forming agent is a polyester polyurethane film-forming agent.

[0091] The lubricant is polyacrylamide.

[0092] The curing temperature is 180° C. and the curing time is 7 hours.

[0093] The pultrusion speed is 300 mm / min.

[0094] The preparation method of the anti-ultraviolet synergist is:

[0095] A1: 3.5 g of 10,13-epoxy-10,12-octadecadienoic acid, 4 g of yttrium nitrate and 200 g of tetrahydrofuran were stirred and mixed, and reacted at 50° C. for 100 min;

[0096] A2: Add 15 g of 1,2-dimercapto-o-carborane, 2 g of 1-(2-propenyl)-2-benzimidazolone, and 4 g of triethylamine, raise the temperature to 63°C and stir for 120 min, and distill off tetrahydrofuran to obtain an anti-ultraviolet synergist.

[0097] The photovoltaic support comprises: columns, main beams, purlins, and struts; the main beams are supported by columns below; the purlins are fixed on the main beams; one end of the struts is fixed on the main beams, and the other end is fixed on the columns.

[0098] Comparative Example 1

[0099] This example is based on Example 1, except that no UV protection enhancer is added.

[0100] Comparative Example 2

[0101] This example is based on Example 1, except that 10,13-epoxy-10,12-octadecadienoic acid is not added.

[0102] Comparative Example 3

[0103] This example is based on Example 1, except that 1,2-dimercapto-o-carborane is not added.

[0104] Table 1 Test results of each case

[0105]

[0106]

[0107] Through the data analysis of the above embodiments and comparative examples, the mechanical properties and durability of the basalt fiber composite photovoltaic bracket material prepared by the present invention are improved.

[0108] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a basalt fiber composite photovoltaic bracket material, the operating steps of which are as follows: S1: by weight, 10-20 parts of basalt fiber are placed in 60-80 parts of bisphenol A epoxy vinyl ester resin and soaked for 10-20 minutes; S2: Continue to add 0.1-0.3 parts of coupling agent, 0.5-1 parts of film-forming agent, 0.3-0.7 parts of lubricant, and 0.5-1 parts of UV protection synergist, and stir and mix evenly to obtain a mixture; S3: pouring the mixture into a mold, heating and curing it into shape, and then cooling it to room temperature; S4: pulling and extruding the formed product into a mold to obtain a basalt fiber composite photovoltaic bracket material; The preparation method of the anti-ultraviolet synergist is: A1: By weight, 0.2-3.5 parts of 10,13-epoxy-10,12-octadecadienoic acid, 1-4 parts of yttrium nitrate, and 100-200 parts of tetrahydrofuran are stirred and mixed, and reacted at 40-50° C. for 30-100 minutes; A2: Add 12-15 parts of 1,2-dimercapto-o-carborane, 0.2-2 parts of 1-(2-propenyl)-2-benzimidazolone, and 2-4 parts of triethylamine, raise the temperature to 50-63°C and stir for 100-120 minutes, and distill off tetrahydrofuran to obtain an anti-ultraviolet synergist.

2. The method for preparing a basalt fiber composite photovoltaic bracket material according to claim 1, characterized in that: The coupling agent is one of KH550, KH560, KH570 and KH792.

3. The method for preparing a basalt fiber composite photovoltaic bracket material according to claim 1, characterized in that: The film-forming agent is one of acrylic resin film-forming agent, butadiene resin film-forming agent, epoxy polyurethane film-forming agent and polyester polyurethane film-forming agent.

4. The method for preparing a basalt fiber composite photovoltaic support material according to claim 1, characterized in that: The lubricant is hexadecyltrimethyl quaternary ammonium bromide or polyacrylamide.

5. The method for preparing a basalt fiber composite photovoltaic support material according to claim 1, characterized in that: The curing temperature is 150-180° C., and the curing time is 4-7 hours.

6. The method for preparing a basalt fiber composite photovoltaic support material according to claim 1, characterized in that: The pultrusion speed is 200-300 mm / min.

7. The method for preparing a basalt fiber composite photovoltaic support material according to claim 1, characterized in that: The photovoltaic support comprises: columns, main beams, purlins, and struts; the main beams are supported by columns below; the purlins are fixed on the main beams; one end of the struts is fixed on the main beams, and the other end is fixed on the columns.

Citation Information

Patent Citations

  • Nonmetal solar photovoltaic support material and preparing method thereof

    CN106589592A

  • Nonmetal solar energy photovoltaic support material and preparation method thereof

    CN110527239A

  • Multi-fiber composite resin-based photovoltaic bracket material and preparation method thereof

    CN111303587A

  • Photosensitive resin composition for liquid crystal display element, color filter using the same, process for manufacture of the color filter, and liquid crystal display element

    CN101233435A

  • Basalt fiber composite-material photovoltaic support profile and photovoltaic panel support manufactured by use of profile

    CN106046694A